Natural Computing 4th International Workshop on Natural Computing Himeji, Japan, September 2009 Proceedings - Peper, F.; Umeo, H.; Matsui, N.; Isokawa, T. (Proceedings in Information and Communications Technology,, 2010)
Most natural and artificial systems transform information in a predictable or programmable way; such transformation can be interpreted as harnessing nature for computing. Recently we have witnessed a burst of research in unconventional computing, resulting in the development of experimental prototypes of natural computers, plasmodium computers, reaction-diffusion processors, and DNA computers as well as theoretical paradigms of natural computation such as cellular automata, artificial chemistry, evolutionary computing, and neural networks. The International Workshop on Natural Computing (IWNC) brings together computer scientists, biologists, mathematicians, electronic engineers, physicists, and others to critically assess present findings in the field, and to outline future developments in nature-inspired computing. This compilation of papers presented at the most recent workshop, held in Nagoya, Japan, makes a valuable contribution to the understanding of natural computing.